2021
DOI: 10.1080/14656566.2021.1960311
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic agents for the management of COVID-19 patients with preexisting cardiovascular disease

Abstract: Introduction The coronavirus disease 2019 (COVID-19) pandemic is the largest public health challenge of the twenty-first century. While COVID-19 primarily affects the respiratory system, manifesting as interstitial pneumonitis and severe acute respiratory distress syndrome (ARDS), it also has implications for the cardiovascular system. Moreover, those admitted to hospital with severe COVID-19 are more likely to have cardiovascular comorbidities such as hypertension and diabetes mellitus. The under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 157 publications
(223 reference statements)
0
9
0
Order By: Relevance
“…Their mechanism of action inhibits circulating PCSK9 protein, thereby blocking degradation of the LDL receptor (LDLR), increasing its expression on the surface of hepatocytes and the uptake of LDL into the liver [ 90 ]. This injectable lipid-lowering therapy is dedicated especially for those with familial hypercholesterolemia (FH) [ 90 , 91 , 92 ]. FH is a genetic condition that causes significant increases in serum cholesterol and LDL-C levels.…”
Section: Lipid-lowering Therapies In Service Of Covid-19 Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Their mechanism of action inhibits circulating PCSK9 protein, thereby blocking degradation of the LDL receptor (LDLR), increasing its expression on the surface of hepatocytes and the uptake of LDL into the liver [ 90 ]. This injectable lipid-lowering therapy is dedicated especially for those with familial hypercholesterolemia (FH) [ 90 , 91 , 92 ]. FH is a genetic condition that causes significant increases in serum cholesterol and LDL-C levels.…”
Section: Lipid-lowering Therapies In Service Of Covid-19 Treatmentmentioning
confidence: 99%
“…FH is a genetic condition that causes significant increases in serum cholesterol and LDL-C levels. FH begins at a noticeably young age and responds poorly to oral therapy, and therefore represents an increased cardiovascular risk for individuals affected [ 92 ].…”
Section: Lipid-lowering Therapies In Service Of Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendelian randomization study found a higher level of ACE-2 receptors to be causally associated to diabetes; this may predispose patients with diabetes to SARS-CoV-2 infection [15]. Furin is a type 1 membranebound protease that is overexpressed in diabetics [16]. This proprotein convertase helps the virus get inside the host cell by reducing SARS-reliance CoV-2's on human proteases.…”
Section: Diabetes and Covid-19mentioning
confidence: 99%
“…As a result, a dysregulated immune response characterized by increased ACE-2receptors and furin expression may result in greater lung inflammation and reduced insulin levels. For diabetic individuals, the virus's easy entrance creates a life-threatening situation [15,16]. Furthermore, decreased T-cell activity and higher levels of interleukin-6 (IL-6) play a key role in the development of COVID-19 illness in diabetics [18].…”
Section: Diabetes and Covid-19mentioning
confidence: 99%